2007
DOI: 10.1590/s0101-20612007000100017
|View full text |Cite
|
Sign up to set email alerts
|

Fortificação de alimentos com o pó da casca de ovo como fonte de cálcio

Abstract: ResumoO pó da casca de ovo é usado como fonte de cálcio em multimisturas distribuídas no Brasil por organizações não-governamentais. O presente trabalho teve por objetivos fortificar, com o pó da casca de ovo, alimentos tradicionais, de baixo custo e de fácil preparo, e estimar a contribuição nutricional de porções desses alimentos para o aporte diário de cálcio. Foram elaboradas dez preparações de consumo habitual, que foram enriquecidas com o pó da casca de ovo (37,4% de cálcio) na proporção de 1 g do pó par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
0
6
0
9
Order By: Relevance
“…However, eggshells are a good calcium resource as a nutritional supplement, which enjoy great business prospects [1,2]. The eggshell calcium carbonate had been traditionally utilized as a fertilizer, soil conditioner or an additive for animal feed due to its high nutrient content [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, eggshells are a good calcium resource as a nutritional supplement, which enjoy great business prospects [1,2]. The eggshell calcium carbonate had been traditionally utilized as a fertilizer, soil conditioner or an additive for animal feed due to its high nutrient content [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The eggshell calcium carbonate had been traditionally utilized as a fertilizer, soil conditioner or an additive for animal feed due to its high nutrient content [3][4][5][6][7][8]. Naves also found that traditional meals fortified with eggshell powder could significantly contribute to the adequate calcium intake and to prevent calcium deficiency, such as osteoporosis, in individuals of different age groups and socioeconomic statuses social levels [1]. Nowadays, there were many researchers whose focus is on calcium organic acid (COA) preparation, such as calcium lactate, calcium pyruvic, calcium acetate, and calcium gluconate.…”
Section: Introductionmentioning
confidence: 99%
“…In this matter, products fabricated by calcium fortification from chicken eggshell waste might contribute recommended dietary intake of calcium for human. Previous report by Naves et al (2007) indicated that the meal fortified with powder of chicken eggshell significantly contributed to the adequate amount of calcium intake and helped in prevention of calcium deficiency. As a good source of dietary calcium, chicken eggshell may serve as an excellent replacer of shells of crustacean origin.…”
Section: Development and Analysis Of Bread Fortified With Calcium Extmentioning
confidence: 99%
“…Ao avaliar do teor de cálcio, observou-se que todas as formulações elaboradas continham níveis de cálcio em sua composição sem a adição do pó da casca de ovos caipiras (ver Tabela 3). Esses resultados estão relacionados tanto ao uso de alimentos fonte de cálcio em suas formulações, como o leite no bolo de trigo, assim como as fontes de cálcio presentes nas farinhas e cereais (NAVES et al, 2007). Com a adição de 1,0% do PCOC nas formulações, observou-se que houve aumento significativo no teor de cálcio nas três formulações avaliadas (ver Tabela 3).…”
Section: Desenvolvimento Das Formulações E Avaliação Físico-químicaunclassified
“…A Portaria nº 27, de 13 de janeiro de 1998 VES et al, 2007;OLIVEIRA et al, 2009). Naves et al, (2007) LÖNNERDAL, 2010). Proposta de uso de alimentos como fontes de cálcio fortificados com ferro tem comprovado aumento das reservas de ferro e suprindo as necessidades de cálcio, consistindo em alternativas viáveis para prevenção de carências nutricionais (SILVA et al, 2002).…”
Section: Desenvolvimento Das Formulações E Avaliação Físico-químicaunclassified